FAKTOR YANG MEMPENGARUHI ASFIKSIA NEONATORUM DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO TAHUN 2009 - Tin Utami; Erni Purwati (Viva Medika, 2010)
Background : Neonatal asphyxia is a condition in babies can not breathespontaneously after birth. This is related to factors that arises in pregnancy,childbirth or soon after birth, if it lasts too much can result in brain damage ordeath. In hospitals Prof. Dr. Margono Soekarjo in 2008 there were 614 cases ofasphyxia with 48 meningggal (7.8%) and in 2009 there were 475 events in 40cases died (8.42%).Objective : The purpose of this study is to identify factors that influence neonatalasphyxia in hospitals Prof. Dr. Margono Soekarjo in 2009.Method : Design of this research is quantitative descriptive with cross sectionalapproach. The population in this study were all newborns with asphyxianeonatrum in hospitals Prof. Dr. Margono Soekarjo Purwokerto 2009. Thesampling technique purposive sampling 82 respondents.Result : Most of asphyxia were as many as 41 respondents (50%). Based on themother's age the majority of respondents aged <20 years with asphyxia were 15respondents (44.1%). Based on birth weight most of the respondents with lowbirth weight with asphyxia were 21 respondents (52.5%). Based on the majority ofrespondents experienced KPD KPD with asphyxia were 34 respondents (51.5%).Based on the majority of respondents maternity deliveries to the action withasphyxia were 28 respondents (47.5%). Based on neonatal factors largelypremature infants with asphyxia respondents were 21 respondents (48.8%).Conclusion : Description of the factors affecting neonatal asphyxia in hospitalsProf. Dr. Margono Soekarjo the year 2009 most of asphyxia were as many as 41respondents (50%). Keyword : Asphyxia, maternal age, birth weight, premature rupture ofmembranes (PROM), type of delivery, premature.